Analysis Of Eligibility, Contribution And Behavior Of Cloves Market In North Kulisusu District, North Buton Regency, Southeast Sulawesi - Wa Ode Al ZARLIANI; La Ode Muhammad DAVID (International Journal of Environmental, Sustainability, and Social Science, 2022)
This research was conducted in Wa Ode Buri Village, North Kulisusu District, and North Buton Regency. The location determination was determined purposively. The objectives of this research are 1) to find out how much income farmers get from farming, which is obtained by farmers from clove farming in Wa Ode Buri Village, North Kulisusu District, and North Buton Regency. 2) To find out how much contribution farmers get from clove farming in Wa Ode Buri Village, North Kulisusu District, North Buton Regency. 3) To find out how much feasibility value is obtained by farmers from clove farming in Wa Ode Buri Village, North Kulisusu District, and North Buton Regency. 4) How is the behavior of the clove market in North Kulisusu District. The sampling technique used is a simple random sampling technique. The results showed that 1) the average income received by respondent farmers from clove farming was IDR 15,258,026 with an income range of IDR 7,098,750 – IDR 29,798,750. 2) The value of the feasibility of farming is obtained by a value of 2.3, which means that the clove farming carried out by the respondent farmers is feasible to be cultivated and developed. 3) The contribution of clove farming income to the total income of farmers is 68.04%, which means that clove farming income is categorized as high.